San Francisco Moments in History The Favorite Fair (Public Service Dept. Office of the Mayor)
On verso: San Francisco celebrated the opening of the Panama Canal in 1915 by hosting the Panama Pacific International Exposition on reclaimed land in the Marina district. On opening day 150,000 jubilant San Franciscans marched behind Mayor, James Rolph to the Fairgrounds. Focal point of the Fair was the 435 foot high Tower of Jewels, its surface bathed at night by the Fair's spectacular searchlight displays.